Comparative Study of Development between Islamic Inheritance Law According to Compilation of Islamic Law (KHI) & Faroid Science - Ninuk Tri Welas (Sultan Agung Notary Law Review, 2021)
The background of this research explains that the Islamic Inheritance Law regulates the matters of inheritance (inheritance) left by the deceased, namely regulating the transfer of inheritance from the deceased (heir) to the living (heir). This study uses an empirical juridical approach, with descriptive analytical specifications of data collected with primary data from field research and secondary data from literature studies, while qualitative data. This research in: (1) Forms of inheritance law that have not been contained in conventional fiqh (fiqh almawarits), but they have been contained and codified in the KHI inheritance law, including: Article 171 concerning Joint Assets, Article 177 concerning the division of fathers `asobah. Article 209 states that adoptive fathers and adopted children receive an inheritance, and if they do not receive a will, then they are entitled to receive a compulsory will. (2) Comparison of Islamic Inheritance Law according to the Compilation of Islamic Law (KHI) with Faroid Science, namely: Indonesia as a developing country which is developing requires uniformity (unification) of law in the form of codification (Written Law). (3) Similarities and Differences in Islamic Inheritance Law According to the Compilation of Islamic Law (KHI) and Faroid Science, which should be used as the main reference in the framework of drafting a Law on KHI. Indonesia as a developing country which is developing requires uniformity (unification) of law in the form of codification (Written Law). (3) Similarities and Differences in Islamic Inheritance Law According to the Compilation of Islamic Law (KHI) and Faroid Science, which should be used as the main reference in the framework of drafting a Law on KHI. Indonesia as a developing country which is developing requires uniformity (unification) of law in the form of codification (Written Law). (3) Similarities and Differences in Islamic Inheritance Law According to the Compilation of Islamic Law (KHI) and Faroid Science, which should be used as the main reference in the framework of drafting a Law on KHI.